Careers and contingencies: Constructing careers in the music and building industries - Bennett, Dawn; Moore, Philip (Common Ground, 2008)
The idea of understanding working life in terms of a "career" may seem commonsense for societies characterised by a complex division of labour and individual progressions through a hierarchy of positions. This is not always the case. The activities, understandings and contingencies associated with many careers are not widely understood, and it is these career-oriented activities and understandings that are apt to be of particular significance in establishing an identity for the worker. In this paper we explore how careers are made and understood in two workplace cultures: the orchestra and the building industry. Our argument is that while these workplaces are structured in very different ways, there are distinct similarities in the constraints and possibilities faced by their respective workforces. Through a comparative account of these two workplace cultures we seek to show that we can better understand each by teasing out ethnographic insights that illuminate features of the other.